CONCEPTE ŞI PRACTICI DE EXTERNALIZARE A SERVICIILOR DE BIBLIOTECĂ : (STUDIU DE CAZ LA BIBLIOTECA PUBLICĂ DE DREPT) - HARJEVSCHI, Mariana; BACAL, Diana (BIBLIOPOLIS, 2020)
The article is an overview on the outsourcing of the library services, offering terminology explanation, including the description of advantages and disadvantages of outsourcing. The author advocates for the implementation of this activity in the library, justifying that they produce savings and improve the quality of library services. Finally, the article presents the experience of the Public Law Library in the partial externalization of loan service in collaboration with the company INCASSO SRL.